Early intervention in psychiatry : EI of nearly everything for better mental health - Byrne, Peter, 1964-; Rosen, Alan, 1946 January 3- (Chichester, West Sussex, UK : John Wiley and Sons Inc., 2014)
"The early recognition and treatment of psychiatric disorders constitutes secondary prevention: to date, the best evidence and best practice has been in EI for psychosis in young people. This new title will inform interventions in people from all age groups, building on the core components of excellent services: holistic, more engaging, low impact, culture- and age-sensitive practices, robust crisis interventions, assertive case management, flexible home visiting, family consulting, and in- and out-of-hours active response services. EI Teams have a low threshold to identify cases, reduce stigma in patients and their local community, engage users and carers in services even if treatment is not indicated or not available, and vigorously treat the first signs of the disorder in the first three years ("the critical period"). In managing a complex mix of possible noncases and cases, medication is only one option and part of phase-specific psychosocial interventions: education, family work, cognitive behavioural therapy, assertive community treatment, substance misuse and vocational interventions, amongst others"--Provided by publisher.
Machine generated contents note: List of contributors -- Foreword -- Part I: The Rationale for Early Intervention in Nearly Everything -- 1 Introduction -- 2 How Early Intervention can turn things upside down and turn a patient into a psychiatrist -- 3 Involving the Family in Early Interventions -- 4 Do Early Intervention Services for Psychosis Represent Value for Money? -- Part II: Early Intervention across the Lifespan -- 5 Perinatal preventive interventions in psychiatry: A clinical perspective -- 6 Psychiatry and Intervention in Infancy and Early Childhood -- 7 Early Intervention for young people with mental illness -- 8 Transiting out of Child and Adolescent Mental Health Services -- 9 Adults of working age -- 10 Early Intervention in Older Adults -- A focus on Alzheimer's Dementia -- Part III: Early Intervention in Specific Settings -- 11 Primary prevention of mental disorders -- 12 Early intervention in mental health problems: the role of the voluntary sector -- 13 Why primary care matters for early intervention in psychiatry -- 14 General hospitals -- 15 Early Intervention Services: Background, rationale and development -- Part IV: Early Intervention in Specific Disorders -- 16 Prevention and early intervention in depression and anxiety disorders -- 17 Alcohol and substance use prevention and early intervention -- 18 Early intervention in childhood disorders -- 19 Early intervention for Delirium -- 20 Early intervention for Self-harm -- 21 Early intervention in Bipolar disorder -- 22 Early intervention in Eating disorders -- 23 Early intervention to reduce violence and offending outcomes in young people with mental disorders -- 24 Early intervention for Borderline Personality Disorder -- Part V: Conclusions -- 25 Early intervention and The Power of Social Movements: UK development of early intervention in psychosis as a social movement and its implications for leadership -- 26 Challenging stigma -- 27 Conclusions including standards -- Afterword.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Mental Disorders -- prevention & control; Early Medical Intervention -- methods; Mental Health Services -- organization & administration; Mental illness -- Diagnosis; Mental illness -- Treatment; Psychiatry; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Mental illness -- Diagnosis; Mental illness -- Treatment; Psychiatry; Electronic books